2007
DOI: 10.1123/ijspp.2.3.292
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Repeated-Effort Test for Elite Men’s Volleyball

Abstract: Purpose:The authors conducted a study to develop a repeated-effort test for international men’s volleyball. The test involved jumping and movement activity that was specific to volleyball, using durations and rest periods that replicated the demands of a match.Methods:A time–motion analysis was performed on a national team and development national team during international matches to determine the demands of competition and thereby form the basis of the rationale in designing the repeated-effort test. An evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 8 publications
4
70
0
8
Order By: Relevance
“…Sheppard et al (2007) and Sheppard et al (2009) identified Middle blocker as the most frequent performer of jumps during block in comparison to Setters and Outsides hitters, while Middle blockers performed more jumps during attack than Outside hitter and Setter, concurring with our study. Vilamitjana et al (2008) reported that the most frequent performer of jumps is Middle blocker, followed by Outside hitter, Setter and Opposite, also concurring with our study.…”
Section: Jumpssupporting
confidence: 79%
See 1 more Smart Citation
“…Sheppard et al (2007) and Sheppard et al (2009) identified Middle blocker as the most frequent performer of jumps during block in comparison to Setters and Outsides hitters, while Middle blockers performed more jumps during attack than Outside hitter and Setter, concurring with our study. Vilamitjana et al (2008) reported that the most frequent performer of jumps is Middle blocker, followed by Outside hitter, Setter and Opposite, also concurring with our study.…”
Section: Jumpssupporting
confidence: 79%
“…Investigations into players' ability to reach upwards, attack frequently from height and achieve a high blocking position showed that jumping is an important athletic skill for high performance in volleyball (Aouadi et al, 2012;Borràs, Balius, Drobnic, & Galilea, 2011;Sheppard, Gabbett, & Taylor, 2007;Sheppard et al, 2008;Vilamitjana et al, 2008). The attack and block, as important actions of a volleyball game, were identified as the best predictors in matches (Afonso, Esteves, Araújo, Thomas, & Mesquita, 2012;Castro & Mesquita, 2008;Marcelino & Mesquita, 2006;Marcelino, Mesquita, & Afonso, 2008;Rodríguez-Ruiz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The frequent jumps performed during volleyball training sessions and games require the ability to preserve power application for a prolonged period of time 1 . As a consequence, the evaluation of explosive strength endurance in volleyball athletes is as important as the evaluation of CMJ performance 18 .…”
Section: Introductionmentioning
confidence: 99%
“…During games and training sessions, hundreds of jumps are performed, especially during attacking and blocking actions 1 . Furthermore, a greater jump height during serving and blocking actions is achieved by the most successful teams with victories of the same competitive level 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation